Waves of El Niño-Southern Oscillation and Influenza Pandemics - Oluwole, Olusegun S. A. (Frontiers in Environmental Science, 2016)
Influenza pandemics have occurred at irregular intervals for over 500 years, unlike seasonal influenza epidemics which occur annually. Although the risk factors are known, the basis for the timing of influenza pandemic waves are unknown. Coherence of peaks of El Niño and influenza pandemic in 2009–2010, however, suggests that both waves are coupled. This study was done to determine the relation of influenza pandemics to the peaks and waveforms of El Niño southern oscillation (ENSO). ENSO cycles from 1871–2015 which had El Niño phases were windowed from Multivariate El Niño Index. Influenza pandemic peaks were mapped to ENSO monthly time series. ENSO waveforms were compared graphically, and fitted to nonstationary cosinor models. Second order polynomial regression model was fitted to the peak and duration of El Niño. Agglomerative hierarchical cluster of ENSO waveforms was performed. All influenza pandemic peaks mapped to El Niño peaks, with lags of 0–5 months. ENSO waveforms during influenza pandemics share parameters of oscillation. Nonstationary cosinor models showed that ENSO cycles are complex waves. There was second order polynomial relationship between peak and duration of El Niños, p < 0.0001. ENSO waveforms clustered into four distinct groups. ENSO waveforms during influenza pandemics of 1889–1900, 1957–1958, and 1968–1969 linked closely. ENSO indices were significantly high from 7–16 months after onset of cycles, p < 0.0001. Surveillance for El Niño events to forecast periods of maximal transmission and survival of influenza A viruses is, therefore, crucial for public health control strategies.